Enhancement of flow boiling using 3D printed porous structures - Tan, Gan Teng (2015)
With the consistently rising demand for better and more efficient electronic systems over the years, there is a need for high-performing microprocessors. However, the increase in performance of the microprocessors is often accompanied with rising heat dissipation. Hence, in order to keep up with future demands and not limit the growth of the microprocessors industry, it is vital to explore methods of cooling to cope with the rate of heat generated. In this project, experimental studies were carried out to investigate the effects of flow rate, heat flux and surface porosity on flow boiling heat transfer. Tests were conducted for two 3D printed porous structures - "Octet" and "Dope" surfaces, inserted in a horizontal rectangular evaporator channel. Heat was channelled from the heater to the base of the evaporator with FC-72 used as the liquid coolant. Pump revolutions, which ranged from 50 to 150 rpm were used to control the flow rate of the coolant, and tested over heat fluxes varying from 8.04 to 97.25 kW/m2. The actual flow rate, wall temperatures, coolant temperatures and pressures were recorded for each experiment. Experimental results showed approximate 56% and 42% enhancements in flow boiling heat transfer coefficients with respect to an empty channel, for the "Octet" and "Dope" surfaces, respectively. It was also observed that increase in flow rate for the "Octet" and "Dope" surfaces resulted in an approximate 28% and 3% enhancement in heat transfer, respectively. The maximum steady state flow boiling heat transfer of 1.50 kW/m2⋅K was obtained with the "Octet" surface, at pump revolution of 100 rpm, which translates to a flow rate of 0.30 L/min.